Amber suppression technology for mapping site-specific viral-host protein interactions in mammalian cells - Isa, Nur Firdaus; Bensaude, Olivier; Murphy, Shona (Bio-protocol LLC, 2022)
Probing the molecular interactions of viral-host protein complexes to understand pathogenicity is essential in modern virology to help the development of antiviral therapies. Common binding assays, such as co-immunoprecipitation or pull-downs, are helpful in investigating intricate viral-host proteins interactions. However, such assays may miss low-affinity and favour non-specific interactions. We have recently incorporated photoreactive amino acids at defined residues of a viral protein in vivo, by introducing amber stop codons (TAG) and using a suppressor tRNA. This is followed by UV-crosslinking, to identify interacting host proteins in live mammalian cells. The affinitypurified photo-crosslinked viral-host protein complexes are further characterized by mass spectrometry following extremely stringent washes. This combinatorial site-specific incorporation of a photoreactive amino acid and affinity purification-mass spectrometry strategy allows the definition of viral-host protein contacts at single residue resolution and greatly reduces non-specific interactors, to facilitate characterization of viral-host protein interactions